SISTEM INFORMASI PENGAJUAN KREDIT ONLINE PADA BIMA FINANCE - YONATHAN SION SYALOM SANTOSA, 12.01.55.0002 (Information Technology and Telematics, 2017)
Abstract- The process of credit application system in the Milky Finance is still done manually whereby if the loan applicant wants to apply for credit, the loan applicant must come first to Bima Finance to fill the loan application form and meet the terms proposed by the Milky Finance. System development method used in this research waterfall with the beginning stages of the system, system analysis, system design using UML, system implementation using PHP and MySQL. The results of this research is the online credit application information systems in the Milky Finance can facilitate credit applicants to apply for the loan without limitation of time and place and makes it easier credit applicants to obtain credit information on the Bima Finance quickly and easily Keywords – Information System, Credit, Online, Bima Finance